Pasantía empresarial en la secretaria de infraestructura de Duitama apoyando actividades de supervisión y control (2023)
The development of the degree project was carried out under the internship modality in the infrastructure department of the Municipality of Duitama, through which support was provided in the performance of administrative and technical activities, among which we find the supervision of works, pre-feasibility reports, preparation of reports and quantity sheets. These activities are carried out based on the stipulations of the manuals, guides and regulations in force regulated by the National Roads Institute or the entity. In order to comply with the works and activities assigned by the entity's supervisor, spreadsheets, technical visits, visual inspections, requests and reports were made, which supported the feasibility of the interventions. In relation to the results obtained in the course of the internship, pathologies with high severity are recognized, which need to be prioritized to avoid the increase of their deterioration, the construction of budgets, analysis of benefits and feasibility are supported to define the feasibility of the interventions under the modality of concerted work. Thanks to the continuous supervision and control, during the execution of the road section of the Juan Grande Neighborhood, it reached an advance of approximately 85%, that is to say, once the internship was completed, the road section is at the granular base level. In conclusion, the development of the internship allowed the works to have a continuous performance, which optimizes the time and scope of the interventions planned by the infrastructure unit.